ANALISIS PENGEMBANGAN AGROFORESTRI DI KECAMATAN LASALIMU KABUPATEN BUTON - safril kasim (Universitas Haluoleo, 2015)
Agroforestry developmet analysis in Lasalimu Regency, Buton District, Southeast Sulawesi province aimed to evaluate existing agroforestry system that has been implemented by local farmers in this area and to provide land use development strategy based on socio economic and land suitability evaluation. Focus Group Discussion (FGD) with local farmers was carried out in Prediagnosis and Diagnosis Phase in order to explore problems and constrains that faced by stakeholders. While Land Suitability Analysis was conducted to develop a proper land use in accordance with its suitability classes. This study found that there are two agroforestry systems based on the existing components, namely agrisilviculture and agrisilvopastura. Problems and constraints encountered by local farmers were lack of education, lack of skills, especially in silviculture aspect, low agribusiness management skill and low acsess to financial sources. Land suitability analysis showed that in general,land suitability ratings for woody crops and perennial crops were categorized as moderately suitable (S2), marginally suitable (S3) and Not Suitable (NS) while those for annual crops / non rice food crops were categorized as marginally suitable (S3) and Not Suitable (NS). The study also found that there are significant land area that are suitable for livestock development through agrosilvopasture system. In conclusion, agroforestry system can be potentially implemented in Lasalimu Regency with on the improvement of local farmers’s capacity and the development of appropriate technology. Key words: agroforestry, focus group discussion, land suitability, land development.